UPAYA PENYELESAIAN POLEMIK RANCANGAN UNDANG-UNDANG KESETARAAN DAN KEADILAN GENDER (RUU KKG) DI INDONESIA - Nethan, Ariel; Ikhtiarin, Ananda Dewin; Agustin, Viola Marsela; Yuel, Maria Veri Diana Baun; Subandi, Yeyen; Nuswantoro, Bagus Subekti (Jurnal Ilmiah Dinamika Sosial, 2022)
The issue of gender equality is an important study in international relations. In Indonesia itself, the issue of gender equality is still rife. Rancangan Undang-Undang Kesetaraan dan Keadilan Gender (RUU KKG) is an initial draft of the government's efforts to enforce gender equality and justice in Indonesia, and this draft law still requires input from the public. RUU KKG has received various responses from the public, ranging from supportive responses to responses against the bill. RUU KKG has urgency considering that in Indonesia there are still frequent acts of gender discrimination, especially against women. This study aims to provide information about the polemics that occur in the Draft Law on Gender Equality and Justice in Indonesia. This study uses a qualitative method in the form of descriptive analysis techniques. The analysis of this research uses a conceptual approach. The result of this research is that information was found regarding the presence of the RUU KKG in Indonesia which later reaped many pros and cons and became a polemic. The polemic of  RUU KKG  was then based on those who said they were pro on the grounds of the positive influence brought by the RUU KKG and those who were against it, especially the Muslim group, on the grounds that there were articles in RUU KKG that contradicted religion. This polemic of the RUU KKG  certainly requires an integrative negotiation effort to find a resolution that can be agreed upon by various parties.